PRINSIP-PRINSIP KESOPANAN DALAM UJARAN MAHASISWA SEMESTER 6 FAKULTAS ILMU BUDAYA UNSRAT; SEBUAH ANALISIS - SIMATUPANG, MEGARIA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2017)
ABSTRACT This research entitled â€œPrinsip Kesopanan dalam Ujaran Mahasiswa Semester 6 Jurusan Sastra Inggris Fakultas Ilmu Budaya: Suatu Analisis Pragmatikâ€ focuses on maxim related to the principle of politeness. The problem of this research are: what kinds of politeness principle are in the utterances used by 6th semesterâ€™s students at English Department Faculty of Humanities and what function of politeness principle are in the utterances used by 6th semesterâ€™s students at English department Faculty of Humanities. The purpose of this research is to identify,clasify,analyze, and describe the function and type of politeness in maxim used that can be shown in daily activities from students in 6th semesterâ€™s English department Faculty of Humanities. In collecting data, the writer concentrates on the utterances which contain the principle of politeness produced by their activities in class. The collected data are analyzed based on Leechâ€™s theory. The result showsÂ  that there are six types of maxim from the utterances of students in 6th semesterâ€™s, they are: tact maxim, generosity maxim, approbation maxi, modesty maxim, agreement maxim and sympathy maxim. It is expected that this research will help students and other readers in learning the pragmatic aspects, especially about maxim in politeness principle. Keyword: Politeness, Utterances, Pragmatic